2014
DOI: 10.1586/14737167.2014.963558
|View full text |Cite
|
Sign up to set email alerts
|

The financial burden of cancer care: do patients in the US know what to expect?

Abstract: Patients in the USA face potentially high financial burdens from the costs of cancer care, distinct from the challenges of societal costs and the economic impact of the disease itself. Survey data suggest that many physicians, let alone many patients, are uninformed about the costs of cancer care. Greater cost transparency and both physician and patient education will be necessary to improve patient understanding of costs and to reduce financial burdens. While many patients wish to discuss costs of care, few r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Conversely, survivors who are unable to meet healthcare expenses may also be proactive in communicating this to their provider and initiating follow-up care discussions for similar reasons. However, these are unlikely explanations given prior research indicating providers’ and patients lack of discussion about costs of care in making decisions about cancer care [19, 20]. Future cancer survivorship research could benefit by examining the role financial hardship plays in delivery of follow-up care in addition to common socioeconomic indicators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, survivors who are unable to meet healthcare expenses may also be proactive in communicating this to their provider and initiating follow-up care discussions for similar reasons. However, these are unlikely explanations given prior research indicating providers’ and patients lack of discussion about costs of care in making decisions about cancer care [19, 20]. Future cancer survivorship research could benefit by examining the role financial hardship plays in delivery of follow-up care in addition to common socioeconomic indicators.…”
Section: Resultsmentioning
confidence: 99%
“…Although insurance has been identified as an important financial factor for receiving high quality cancer treatment, providers and survivors may be unaware of the costs for survivorship care, and patients may move forward with care regardless of payment by the insurer [20]. Additionally, this finding may relate to how MEPS collects data on insurance: Participants are asked their insurance status at the time of the survey, which may not coincide with their cancer episode.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for direct non-medical costs have been found to include costs generated from travel and parking, increased household bills, new clothing, healthier food, household-and childcare-related services, fitness classes, relocation, house modifications and family and friends (Amir, Wilson, Hennings, & Young, 2012;Céilleachair et al, 2012;Longo, Fitch, Grignon, & McAndrew, 2016;McGrath, 2016b;Moffatt, Noble, & Exley, 2010;Timmons, Gooberman-Hill, & Sharp, 2013b). Knowledge of the expected costs is crucial for cancer patients to reduce their financial distress (Peppercorn, 2014) because experiencing a higher than expected financial burden has been found to increase experiences of financial distress (Chino et al, 2017). Furthermore, a study analysing the viewpoints of oncology navigators found that they were aware of the high financial burden of their patients but had insufficient knowledge to address this issue (Spencer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although great strides have been made to localize the dose of radiation to the cancer, normal tissues and organs still often are subjected to a substantial dose of radiation as part of treatment, which can result in significant complications. While radiotherapy is often curative, the adverse effects resulting from treatment can place a major financial burden on both individuals as well as the health care system 10 .…”
Section: Introductionmentioning
confidence: 99%